Effect duration of the initial course of peroneal electrical Transcutaneous NeuroModulation in patients with overactive bladder - Rejchrt, Michal; Krhut, Jan; Gärtner, Marcel; Blok, Bertil F M; Zvara, Peter (World journal of urology, 2023)
PURPOSE: The aim of this prospective 12-month follow-up study is to evaluate the persistence of the treatment effect achieved during the initial course of peroneal electrical Transcutaneous NeuroModulation (peroneal eTNM®) in patients with overactive bladder (OAB). METHODS: This study enrolled 21 female patients who participated in two previous clinical studies designed to assess the efficacy and safety of peroneal eTNM®. The patients were left without subsequent OAB treatment and were invited to attend regular follow-up visits every 3 months. The patient's request for additional treatment was considered an indicator of the withdrawal of the treatment effect of the initial course of peroneal eTNM®. The primary objective was the proportion of patients with persisting treatment effect at follow-up visit 12 months after initial course of peroneal eTNM®. Descriptive statistics are presented using median, correlation analyses were computed using a nonparametric Spearman correlation. RESULTS: The proportion of patients with persistent therapeutic effect of the initial course of peroneal eTNM® was 76%, 76%, 62% and 48% at 3, 6, 9 and 12 months, respectively. There was a significant correlation between patient reported outcomes and the number of severe urgency episodes with or without urgency incontinence as reported by patients at each follow-up visit (p = 0.0017). CONCLUSION: The treatment effect achieved during the initial phase of peroneal eTNM® persists for at least 12 months in 48% of patients. It is likely that the duration of effects is dependent on the length of the initial therapy.
Keywords: transkutánní elektrická neurostimulace; Peroneal nerve; hyperaktivní močový měchýř; Humans; Overactive bladder; následné studie; Female; výsledek terapie; Effect persistence; lidé; Transcutaneous Electric Nerve Stimulation; Electric Stimulation Therapy; URIS® device; ženské pohlaví; Treatment Outcome; Urgency; prospektivní studie; Peroneal electrical Transcutaneous NeuroModulation; elektrostimulační terapie; Follow-Up Studies; Urinary Bladder, Overactive; Prospective Studies